Application of Preference Selection Index (PSI) Method in Selecting Outstanding Students - Yusuf Akhlun Nazzar; Shinta Puspasari; Lastri Widya Astuti (bit-Tech, 2025)
This study aims to develop an objective and transparent system for selecting outstanding students at MTsN 2 Palembang by applying the Preference Selection Index (PSI) method. Conventional evaluation in schools often prioritizes academic performance while overlooking extracurricular involvement and religious achievements. To address this limitation, three main criteria academic achievement, non-academic activities, and tahfidz were integrated into a multi-criteria decision-making framework. The research involved several stages: determining criteria and weights (0.5 for academics, 0.3 for non-academics, and 0.2 for tahfidz), collecting and normalizing data, calculating preference values, and ranking students. Data from 189 students were processed, producing PSI scores ranging from 0.6703 to 0.8329, with an average of 0.7251 and narrow gaps among the top five students. The results showed that although grade IX students dominated the top ten rankings, a grade VIII student achieved the highest score of 0.8329, demonstrating that balanced performance across criteria can outweigh seniority. These findings highlight the effectiveness of PSI in ensuring fair and holistic rankings by recognizing diverse dimensions of student performance, unlike conventional teacher-based assessments. Furthermore, the study illustrates the broader applicability of PSI as a decision-support tool that can be adopted by other schools and educational institutions to align evaluation practices with institutional values and educational goals. This approach not only improves fairness and transparency in student selection but also encourages the design of balanced development programs that foster intellectual, social, and spiritual growth.